Histopathologic Features of Trachea and Lungs in Chickens with Chronic Respiratory Disease - Annisa, Aiza; Darmawi, Darmawi; Etriwati, Etriwati; Balqis, Ummu; Salim, M. Nur; Nazaruddin, Nazaruddin; Aliza, Dwinna; Aisyah, Siti; Awaluddin, Awaluddin; Hasan, Denny Irmawati; Akmal, Muslim; Helmi, T. Zahrial; Asmilia, Nuzul (Jurnal Medika Veterinaria, 2024)
The purpose of this case study is to determine the changes that exist in chickens infected with Chronic Respiratory disease (CRD). A broiler male chicken aged 40 days was found dead in a chicken basket at Ulee Kareng chicken slaughterhouse in a state of feather loss and feces attached to cloaca, on January 6th, 2023. The chicken was brought to pathology laboratory of Faculty of Veterinary Medicine, Universitas Syiah Kuala for necropsy and organ collection. Organs associated with CRD cases were trachea and lungs and histopathological preparations were carried out, stained with Haematoxylin Eosin, and observed under a microscope. The results of histopathological examination showed hemorrhage and hyperplasia of the tracheal epithelium. Hemorrhage was caused by edema which causes increased vascular permeability and epithelial cell hyperplasia occured due to the body's response to infection or inflammation. In the lungs there was bleeding due to damage to the blood vessel wall which caused increased vascular permeability, so that fluid and blood plasma come out of the blood vessels. Fibrinogen then underwent polymerization which resulted in fibrinous thrombi. Congestion happened as the result of fluid accumulation in a location that occured in a passive process so the fluid failed to escape. Because of the accumulation of fluid (congestion), the blood supply to the lung tissue is interrupted, resulting in several points of necrosis in the lungs.